Demographic Challenges in Central and Eastern Europe in 21st Century - Durasiewicz, Arkadiusz (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Due to the fact that the least favorable situation in terms of population is in the countries of Central and Eastern Europe, the article presents the demographic position of these countries, the challenges and risks associated with the demographic crisis, the existing policy guidelines for families and points to the long-term perspective to the next 60 years (graying society). The aim of this article is to present the scale of the demographic crisis but also describe the consequences associated with it, and the challenges faced by each country in the future in the relation to the aging population. The research methods used in this work is desk research, analysis and interpretation of available statistical data and descriptive method based on the available literature.